Pengaruh Beauty Vlogger “X” Terhadap Perilaku Tata Rias Wajah Mahasiswi (Studi Pada Program Studi Usaha Perjalanan Wisata Universitas Negeri Jakarta) - Sevita Putri Hertian; Eti Herawati; Dwi Atmanto (Journal on Education, 2024)
Student are expected to be able to apply makeup to support a professional appearance in the word of tourism. This encourages female students to learn independently, one of which is through beauty vlogger videos on YouTube. The presence of beauty vloggers influences the opinions and skills of female student through uploaded videos. This study aims to determine the effect of beauty vlogger “X” on the makeup behavior of female students (study on Travel Business Study Program, Faculty of Social Sciences, Jakarta State University). The research method uses causality quantitative research and purposive sampling technique. The population of female students class of 2020-2022 was 132 people, and the research sample was 57 people. Data obtained from questionnaires and processed using the Simple Linear Regression Test. The result show Y=17,322+0,601X where the beauty vloggers is 0,601, which means that every increase in the makeup behavior of female students increases by 0,601 with the t value is 8,522 > 2,004 and a significance of 0,000<0,05. Then the null hypothesis (Ho) is rejected and (Ha) is accepted which states that there is an influence of beauty vlogger “X” on the makeup behavior of female students with the contribution of the coefficients of determination (R2) 56,9% on the makeup behavior of female students. The remaining 43,1% is influenced by other variables or factors not examined in this study.